THEMES OF DISPLACEMENT AND IDENTITY OF VIKRAM LALL IN M.G. VASSANJI’S NOVEL THE IN-BETWEEN WORLD OF VIKRAM LALL - Dongre, Manoj; Lalwani, Neeta (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The issue of migration, displacement or dislocation is not new. From the beginning man has been moving across the globe in search of a job or for safety reasons. The In-Between World of Vikram Lall by M.G. Vassanji examines the difficulties of displacement and identity in the post-colonial Kenyan setting, where diasporic peoples' lives are shaped by historical, political, and cultural factors. Vikram Lall, the protagonist is the man divided between several identities and commitments. The journey of Vikram Lall, which reflects the larger story of South Asian immigrants in East Africa is examined in this novel. The story expertly combines themes of identity negotiation in the face of changing socio-political environments, displacement and belonging. In his novel The In-Between World of Vikram Lall Vassanji uses the idea of migration both psychological and physical to emphasize the conflict and confusion that diasporic people go through. The protagonist Vikram battles to settle his mixed identity arose between his colonial Kenyan childhood, his Indian ancestry, and his ultimate banishment to Canada. His journey is placed within the larger framework of Kenyan history and the effects of colonialism, which highlights how the personal and political intertwine to shape diasporic identities in the novel.